An effective photocatalytic hydrogen evolution strategy based on tunable band gap (CuIn)xZn2(1−x)S2 combined with amorphous molybdenum sulfide. (12th April 2021) - Cao, Yanren; Li, Haiyan; Jin, Jingyi; Li, Yanxin; Feng, Ting; Wang, Wei; Dong, Bohua; Cao, Lixin
Abstract : The combination of crystalline band-tunable (CuIn) x Zn2(1− x ) S2 and amorphous a-MoS x provides a good strategy for photocatalysts. Abstract : Fully utilizing the visible light and lowering the economic costs are the toughest challenges of photocatalytic water splitting. To address these issues, a non-noble metal photocatalyst, (CuIn) x Zn2(1− x ) S2 solid solution with an adjustable band gap by modifying its composition, was synthesized. In addition, amorphous molybdenum sulfide (a-MoS x ) was compounded as a co-catalyst on the surface of the solid solution. Compared with crystalline molybdenum sulfide (MoS2 ), a-MoS x can provide more active sites and reduce the activation energy of hydrogen evolution reactions more effectively. The (CuIn)0.2 Zn1.6 S2 (CIZS) photocatalyst loaded with 3 wt% a-MoS x exhibited the best photocatalytic performance with a hydrogen evolution rate of 2100 μmol g −1 h −1 .